GP management of community-acquired pneumonia in Italy: the ISOCAP study - Sanguinetti, C.M.; De Benedetto, F.; Donner, C.F. (Monaldi Archives for Chest Disease, 2005)
Background. Community-Acquired Pneumonia (CAP) is still a significant problem in terms of incidence, mortality rate, particularly in infants and the elderly, and socioeconomic burden. General Practitioners (GPs) are the first reference for patients with this disease, but there are few published studies regarding the outpatient treatment of CAP. Methods. The ISOCAP study aimed to identify the type and outcome of the diagnostic-therapeutic management of CAP by GPs in Italy, within the framework of developing a closer interrelationship between GPs and pulmonary specialists. Thirty-six Pulmonary Divisions throughout Italy each contacted 5 local GPs who agreed to recruit the first 5 consecutive patients who consulted them for suspected CAP within the study’s 1-year observation period. Results. A total of 183 GPs took part in the study and enrolled, by the end of the observation period, 763 CAP patients; of these, complete data was available for 737 patients [males=373, females=364, mean age (±SD) 58.8±19.6 years]. 64.4% of patients had concomitant diseases, mainly systemic arterial hypertension and COPD. Diagnosis of CAP was based by GPs on physical examination only in 41.6% of cases; in the remaining chest X-ray was also performed. In only 4.6% of patients were samples sent for microbiological analysis. All patients were treated with antibiotics: 76.7% in mono-therapy, 23.3% with a combination of antibiotics. The antibiotic class most prevalently used in mono-therapy was cephalosporin, primarily ceftriaxone; the most frequently used combinations were cephalosporin+macrolide and cephalosporin+quinolone. Mono-therapy was effective in 70% of cases, the combination of two or more antibiotics in 91.2% of patients. Overall treatment efficacy was 94.7%; hospitalisation was required in 8.5% of cases. Conclusions. Outpatient management of CAP by GPs in Italy is effective, hospitalisation being necessary only in the most severe cases due to age, co-morbidities or extent of pneumonia. This signifies a very significant savings in national health costs.